TAZKIYATUN NAFS SEBAGAI PARADIGMA INTEGRATIF: MENGURAI KRISIS KARAKTER DALAM PUSARAN TEKNOLOGI ABAD KE-21 - Musyanti Waqiyatul Lana; Rizki Majmatuz Zahiroh; Fitria Wulandari; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The acceleration of technology in the 21st century has created a discrepancy between technical competency achievements and the moral-spiritual character resilience of students. This study aims to examine the relevance of Al-Ghazali’s concept of Tazkiyatun Nafs (purification of the soul) as a value architecture in contemporary character education. Using library research and philosophical analysis, this study dissects how takhalli (renunciation of negative traits), tahalli (cultivation of virtues), and tajalli (actualization of values) can function as integrative mechanisms to respond to identity crises and ethical fragility in the digital era. The findings demonstrate that Al-Ghazali’s thought transcends mere cognitive orientation by emphasizing robust emotional-spiritual development. This integration offers a comprehensive curriculum-pedagogy framework, enabling students not only to be digitally proficient but also to possess integrity, responsibility, and social awareness grounded in adab (ethical refinement). Thus, Tazkiyatun Nafs serves as a therapeutic solution for reorienting character education amidst the vortex of modern moral challenges. Abstrak : Akselerasi teknologi di abad ke-21 telah menciptakan diskrepansi antara pencapaian kompetensi teknis dan ketangguhan karakter moral-spiritual peserta didik. Penelitian ini bertujuan untuk menguji relevansi konsep Tazkiyatun Nafs (penyucian jiwa) Al-Ghazali sebagai arsitektur nilai dalam pendidikan karakter kontemporer. Menggunakan metode studi kepustakaan dan analisis filosofis, penelitian ini membedah bagaimana takhalli, tahalli, dan tajalli dapat difungsikan sebagai mekanisme integratif untuk merespons krisis identitas dan kerapuhan etika di era digital. Hasil penelitian menunjukkan bahwa pemikiran Al-Ghazali melampaui orientasi kognitif semata dengan menekankan pengembangan emosional-spiritual yang kokoh. Integrasi ini menawarkan kerangka kurikulum-pedagogi yang komprehensif, memungkinkan peserta didik tidak hanya cakap secara digital, tetapi juga memiliki integritas, tanggung jawab, dan kesadaran sosial yang berlandaskan adab. Dengan demikian, Tazkiyatun Nafs berperan sebagai solusi terapeutik untuk mereorientasi pendidikan karakter di tengah pusaran tantangan moral modern.